Oral care experiences of palliative care patients, their relatives/carers and healthcare professionals. (2nd December 2021) - Delgado, Maria Bernardes; Plessas, Anastasios; Burns, Lorna; Neilens, Helen; Griffiths, Sarah; Latour, Jos
Abstract : Aim: To explore the oral care experiences of palliative care patients and of those who support or deliver oral care to these patients: nurses, doctors, dentists, their relatives and carers. Data Sources: An electronic search of the databases included: Embase, MEDLINE, DOSS, AMED and PsycINFO was performed. Data selection: Six articles were included in the final synthesis. Data extraction: Thematic analysis was applied by two researchers. Data synthesis: Three themes were identified: 'performing oral care', 'effects on oral health' and 'challenges in palliative care'. Conclusions: Despite similarities of oral care experiences, this review identified some differences, crucially in terms of the wider impact of oral symptoms, namely social interactions with others and challenges to oral care. This confirms the need to investigate these topics further in relation to different stakeholders, such as nurses; and to have consistent guidance to facilitate the provision of effective oral care to palliative care patients.